Assessment of Knowledge and Practice of Various Eye Diseases in Sulaimani: A Descriptive Study - M. Ibrahem, Abdulrahman; Q. Mahmood, Salah; Babakir-Mina, Muhammed; Ibrahim Ali, Salar; Kamal Talabany, Bakhtyar (Kurdistan Journal of Applied Research, 2018)
Knowledge and practice of public, especially patients about eye diseases are important to reduce magnitude of human blindness. Vision and sight are very essential because they allow us to connect to each other’s. In accordance to the recently published data; the estimation of 253 million people lives with vision impairment, 36 million are blind and 217 million suffer from moderate to severe vision impairment. A descriptive cross-sectional study was conducted at Shahid Dr. Aso Hospital in Sulaimani city-Iraq, from April to August 2017 by face-to-face interview through close ended questionnaire for data collecting. All data were analyzed by Statistical Package for Social Sciences version 22.0 software. P-value of < 0.05 was considered as a statistically significant. A total of 430 patients were randomly chosen to participate in the study. They were 254 (59.1%) males and 176 (40.9%) females. 76.7% of respondents was worrying about vision loss, 0.7% was worrying about hair loss. Of the participants, 32.8% was with a good knowledge level and 40.5% was with a poor knowledge level, as well as 3.1% was in a good practice and 58.8% was in a poor practice level. Female knowledge mean score was 9.53±4.96 and male knowledge mean score was 8.42±5.45, the practice mean score of males was 4.33±1.96 and mean practice score of females was 4.13±1.93. The study data indicate the worrying of participates about vision loss is in the highest proportion and the awareness and practice of patients about eye diseases is unsatisfactory. Health education campaigns are needed to improve personal awareness about vision related problems and for better eye health.